2010
DOI: 10.1016/j.jbiomech.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of cartilaginous tissues engineered from infrapatellar fat pad-derived mesenchymal stem cells

Abstract: Articular cartilage has a poor intrinsic capacity for self repair. The advent of autologous chondrocyte implantation has provided a feasible method to treat cartilage defects.However, the associated drawbacks with the isolation and expansion of chondrocytes from autologous tissue has prompted research into alternative cell sources such as mesenchymal stem cells (MSCs) which have been found to exist in the bone marrow as well as other joint tissues such as the infrapatellar fat pad (IFP), synovium and within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 64 publications
4
79
2
1
Order By: Relevance
“…Cartilage tissue engineering studies using chondrocytes (Byers et al 2008), and more recently synovium derived stem cells (Sampat et al 2011), have demonstrated that withdrawal of TGF-from the media after 2-3 weeks of culture enhances long-term matrix accumulation. In this study the withdrawal of TGF-after 21 days did not enhance the subsequent functional development of the engineered construct, consistent with our previous findings (Buckley et al 2010b). A strategy of withdrawing TGF-from the culture media may eventually overcome the problem of diminishing matrix synthesis in long-term culture, but may depend, among other factors, on further optimization of stem cell isolation and expansion conditions (Sampat et al 2011) and the cell seeding density (Huang et al 2009).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Cartilage tissue engineering studies using chondrocytes (Byers et al 2008), and more recently synovium derived stem cells (Sampat et al 2011), have demonstrated that withdrawal of TGF-from the media after 2-3 weeks of culture enhances long-term matrix accumulation. In this study the withdrawal of TGF-after 21 days did not enhance the subsequent functional development of the engineered construct, consistent with our previous findings (Buckley et al 2010b). A strategy of withdrawing TGF-from the culture media may eventually overcome the problem of diminishing matrix synthesis in long-term culture, but may depend, among other factors, on further optimization of stem cell isolation and expansion conditions (Sampat et al 2011) and the cell seeding density (Huang et al 2009).…”
Section: Discussionsupporting
confidence: 89%
“…We have previously shown that MSCs isolated from infrapatellar fat pad tissue are a viable alternative cell source for cartilage tissue engineering (Buckley et al 2010a;Buckley et al 2010b;Vinardell et al 2010). It is evident from the literature that stem cell expansion conditions can significantly influence their subsequent chondrogenic capacity (Tsutsumi et al 2001;Bianchi et al 2003;Solchaga et al 2005;Khan et al 2008;Solchaga et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASCs from infrapatellar fat pad (IPFP) are a promising source of stem cells for chondrogenesis (Wickham et al, 2003;Khan et al, 2007;Khan et al, 2008) and cartilage tissue engineering (Dragoo et al, 2003;Jurgens et al, 2009;Buckley et al, 2010). Our recent study assessed whether DSCM expansion could improve ASC proliferation and chondrogenic potential (He and Pei, 2011a).…”
Section: Pei Et Al Decellularized Stem Cell Matrix For Cell Expansionmentioning
confidence: 99%
“…Mesenchymal stem cells or multipotent stromal cells (MSCs) isolated from various tissues such as bone marrow [1][2][3][4][5][6][7], subcutaneous fat [8][9][10][11], infrapatellar fat pad (IFP) [6,[12][13][14][15][16][17][18][19][20][21] and synovium [9,[22][23][24][25][26], combined with various scaffolds and hydrogels, have been explored for tissue regeneration. The IFP is a particularly attractive source of MSCs for this type of application as it is easy to access and provides a large number of cells with the potential to generate cartilaginous tissue [12,13,20].…”
Section: Introductionmentioning
confidence: 99%